Does Peirce Beg Questions against Conceptualism? - Kasser, Jeff (Transactions of the Charles S. Peirce Society)
In a recent paper exploring tensions between Peirce's theory of inquiry and his philosophy of probability, Stewart and Sterkenburg note persistent textual evidence suggesting that Peirce simply dismisses views that construe probabilities in terms of degrees of belief. Though they stop short of accusing Peirce of begging relevant questions, their discussion invites attention to whether Peirce genuinely argues against conceptualist approaches to probability, and if so, how he does so. This paper clarifies Peirce's target, presents the considerations he offers against conceptualism, and assesses them.